Analysis of Teaching Material Needs for Short Story Writing with the Utilisation of Artificial Intelligence (AI) for High School Students - Rizkia, Muhamad Fajar; Purwahida, Rahmah; Oktaviani, Reni; Purbarani, Etsa; Nanda, Ayu Puspa (Sebatik, 2025)
This research aims to develop short story writing teaching materials based on Artificial Intelligence (AI). Literacy skills are developed in various learning activities, one of which is writing, which can be linked to fictional stories in the form of short stories. This writing activity is related to the use of language in daily life, and the topics raised can be related to everyday experiences. Writing short stories requires a process of developing students' creativity. This process contains the concept that short story writing skills are not acquired instantly, but rather thru a step-by-step process with intensive and continuous practice, and requires students' active participation in the writing process. Writing short stories is not easy and can encounter obstacles such as developing ideas, describing the core of the story, setting, characters, plot development, and building dialog that fits the story and the characters being portrayed. One solution that can be implemented is providing teaching materials with the assistance of Artificial Intelligence (AI). The presence of AI-assisted teaching materials in writing short stories can help someone develop the ideas they want to turn into a short story, the general outline of the story, characters, setting, events, and dialog. This can help someone develop short stories with more varied, creative narratives tailored to each individual's experiences. Thru this AI-based learning material, one can utilize it and elaborate it into a form of self-understanding description that will later be developed or can become points in a specific schema format. The short story writing teaching materials created based on this needs analysis will later be developed, validated, and field-tested on a limited scale.